Corporate debt in Latin America and its macroeconomic implications. Issue 3 (3rd July 2019) - Caldentey, Esteban Pérez; Favreau Negront, Nicole; Méndez Lobos, Luis
Abstract: This article provides an empirical analysis of nonfinancial corporate debt in six large Latin American countries (Argentina, Brazil, Chile, Colombia, Mexico, and Peru), distinguishing between bond-issuing and nonbond-issuing firms, and assessing the debt's macroeconomic implications. The paper uses a sample of 2, 241 firms listed on the stock markets of their respective countries, comprising 34 sectors of economic activity for the period 2009–2016. On the basis of liquidity, leverage, and profitability indicators, it shows that bond-issuing firms are in a worse financial position relative to nonbond-issuing firms. Using Minsky's hedge/speculative/Ponzi taxonomy for financial fragility, we argue that there is a larger share of firms that are in a speculative or Ponzi position relative to the hedge category. Also, the share of hedge bond-issuing firms declines over time. Finally, the article presents the results of estimating a nonlinear threshold econometric model, which demonstrates that beyond a leverage threshold, firms' investment contracts while they increase their liquidity positions. This has important macroeconomic implications since the listed and, in particular, bond-issuing firms (which tend to operate under high leverage levels) represent a significant share of assets and investment. This finding could account, in part, for the retrenchment in investment that the sample of countries included in the paper have experienced in the period under study and highlights the need to incorporate the international bond market in the analyses of monetary transmission mechanisms.